2014
DOI: 10.5152/akd.2014.4825
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeic acid phenethyl ester on isoproterenol-induced myocardial injury in hypertensive rats

Abstract: Objective: The aim of this study is to investigate the effects of caffeic acid phenethyl ester (CAPE) on isoproterenol (ISO)-induced myocardial injury in hypertensive rats. Methods: Rats were divided into 4 groups (n=29):n=7) and L-NNA+ISO+CAPE (L-NNA+ISO + caffeic acid phenethyl ester) group (n=6). ISO (150 mg/kg/day) was given intraperitoneally (i.p.) once a day for 2 consecutive days (at the 12 th and 13 th days of L-NNA treatment). NG-Nitro-L-arginine (L-NNA) was given orally (25 mg/kg/ day) in drinking wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In accordance with our results, Ilhan et al shown that SOD and CAT enzyme activities decreased when compared to control group. 43 There were significantly decreased GPX levels in the ISOtreated group when compared to the control, DEX+ISO and ISO+DEX groups. In parallel to our results, Panda and Kar 44 reported that GPX declined significantly in ISOtreated rats as compared to the respective values of normal control rats.…”
Section: Discussionmentioning
confidence: 84%
“…In accordance with our results, Ilhan et al shown that SOD and CAT enzyme activities decreased when compared to control group. 43 There were significantly decreased GPX levels in the ISOtreated group when compared to the control, DEX+ISO and ISO+DEX groups. In parallel to our results, Panda and Kar 44 reported that GPX declined significantly in ISOtreated rats as compared to the respective values of normal control rats.…”
Section: Discussionmentioning
confidence: 84%
“…Our results were in agreement with many authors; Li et al, (48) reported a significant increase in the levels of lipid peroxidation products (MDA) in ISOinduced rats due to oxidative damage and increased production of free radicals. İlhan et al, (49) demonstrated that, a decrease in SOD and CAT activities in ISO given rats and oxidative stressmediated possible MI. This is due to the fact that excessive superoxide anions may inactivate SOD enzyme, which convert superoxide anion free radicals (O 2 -) to H 2 O 2 and to molecular oxygen (50) .…”
Section: Histological Studies In All Studied Groupsmentioning
confidence: 99%
“…On the one hand, CAPE may have a positive inotropic agent (induction of beta adrenergic receptor by NO) and promote coronary vasodilation by increasing cardiac output; on the other hand it may decrease peripheral resistance by its vasorelaxant effect. In this way, the mean blood pressure might remain stable (Ilhan et al, 2014). For this reason, the effect of CAPE and other CA derivatives on hemodynamics should be clarified in vivo by simultaneously assessing perfusion and blood pressure.…”
Section: Caffeic Acid Phenethyl Estermentioning
confidence: 99%